Biochemical composition of temperate and Arctic populations of Saccharina latissima after exposure to increased pCO2 and temperature reveals ecotypic variation - Olischläger, Mark; Íñiguez Moreno, Concepción; López-Gordillo, Francisco Javier; Wiencke, Christian (Springer, 2014)
Previous research suggested that the polar and temperate populations of the kelp Saccharina latissima represent different ecotypes. The ecotypic differentiation might also be reflected in their biochemical composition (BC) under changing temperatures and pCO2. Accordingly, it was tested if the BC of Arctic (Spitsbergen) and temperate S. latissima (Helgoland) is different and if they are differently affected by changes in temperature and pCO2. Thalli from Helgoland grown at 17 °C and 10 °C and from Spitsbergen at 10 °C and 4 °C were all tested at either 380, 800, or 1,500 µatm pCO2, and total C-, total N-, protein, soluble carbohydrate, and lipid content, as well as C/N-ratio were measured. At 10 °C, the Arctic population had a higher content of total C, soluble carbohydrates, and lipids, whereas the N- and protein content was lower. At the lower tested temperature, the Arctic ecotype had particularly higher contents of lipids, while content of soluble carbohydrates increased in the Helgoland population only. In Helgoland-thalli, elevated pCO2 caused a higher content of soluble carbohydrates at 17 °C but lowered the content of N and lipids and increased the C/N-ratio at 10 °C. Elevated pCO2 alone did not affect the BC of the Spitsbergen population. Conclusively, the Arctic ecotype was more resilient to increased pCO2 than the temperate one, and both ecotypes differed in their response pattern to temperature. This differential pattern is discussed in the context of the adaptation of the Arctic ecotype to low temperature and the polar night.
Keywords: Algas; Chemical composition; CO2; DIC; Ecotype; Global Change; Macroalgae; Saccharina; Temperature